The educational development of university teachers: mapping the landscape - Bélisle, Marilou; Jean, Valérie; Fernandez, Nicolas (Frontiers in Education, 2024)
This article presents the results of a scoping review designed to explore the current state of knowledge about the educational development of university teachers. More specifically, the study examined the definitions attributed to educational development, its aims, the factors that foster it and the variables studied in this field. A thematic analysis was conducted on 98 scholarly documents published between 2000 and 2022. The results indicate that the field of educational development is mainly characterized by ideological and political rather than scientific dimensions. Consequently, the focus is on desired changes in educational development, reflecting a high degree of desirability. Furthermore, the results highlight the individualistic nature of the starting point of professional learning process, suggesting that institutional conditions and resources should be adapted to accommodate the diversity of learning trajectories. This study contributes to a comprehensive understanding of the complex landscape surrounding the educational development of university teachers, highlighting the need for nuanced approaches to promote teaching quality and professional development in the context of higher education.